Objectively measured sleep characteristics and prevalence of coronary artery calcification: the Multi-Ethnic Study of Atherosclerosis Sleep study. Issue 9 (8th July 2015) - Lutsey, Pamela L; McClelland, Robyn L; Duprez, Daniel; Shea, Steven; Shahar, Eyal; Nagayoshi, Mako; Budoff, Matthew; Kaufman, Joel D; Redline, Susan
Abstract : Background: We tested whether objectively measured indices of obstructive sleep apnoea (OSA) and sleep quality are associated with coronary artery calcification (CAC) prevalence independent of obesity, a classic confounder. Methods: 1465 Multi-Ethnic Study of Atherosclerosis participants (mean age 68 years), who were free of clinical cardiovascular disease, had both coronary CT and in-home polysomnography and actigraphy performed. OSA categories were defined by the Apnea-Hypopnea Index (AHI). Prevalence ratios (PRs) for CAC >0 and >400 (high burden) were calculated. Results: Participants with severe OSA (AHI ≥30; 14.6%) were more likely to have prevalent CAC, relative to those with no evidence of OSA, after adjustment for demographics and smoking status (PR 1.16; 95% CI 1.06 to 1.26), body mass index (1.11; 1.02 to 1.21) and traditional cardiovascular risk factors (1.10; 1.01 to 1.19). Other markers of hypoxaemia tended to be associated with a higher prevalence of CAC >0. For CAC >400, a higher prevalence was observed with both a higher arousal index and less slow-wave sleep. Overall, associations were somewhat stronger among younger participants, but did not vary by sex or race/ethnicity. Conclusions: In this population-based multi-ethnic sample, severe OSA was associated with subclinical coronary artery disease (CAC >0), independent of obesity and traditional cardiovascular risk factors. Furthermore, the associations of the arousal index and slow-wave sleep with high CAC burden suggest that higher nightly sympathetic nervous system activation is also a risk factor. These findings highlight the potential importance of measuring disturbances in OSA as well as sleep fragmentation as possible risk factors for coronary artery disease.